2022
DOI: 10.3389/fimmu.2022.887048
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Related to 5-Fluorouracil Based Chemotherapy for Colorectal Cancer

Abstract: BackgroundColorectal cancer (CRC) is one of the most common malignancies and its incidence and mortality are increasing yearly. 5-Fluorouracil (5-FU) has long been used as a standard first-line treatment for CRC patients. Although 5-FU-based chemotherapy is effective for advanced CRC, the consequent resistance remains a key problem and causes the poor prognosis of CRC patients. Thus, there is an urgent need to identify new biomarkers to predict the response to 5-FU-based chemotherapy.MethodsCRC samples were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…For the treatment of CRC, 5-FU continues to be among the most popular and effective chemotherapeutic medicines ( Glimelius et al, 2021 ), and the adjuvant therapy based on 5-FU is essential to CRC patients in stage II-IV after radical surgery, which could prolong the survival time of CRC patients ( Wilkinson et al, 2010 ; Miller et al, 2019 ; Huang X et al, 2022 ). The emergence of chemoresistance remains a significant barrier to long-term benefit ( Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of CRC, 5-FU continues to be among the most popular and effective chemotherapeutic medicines ( Glimelius et al, 2021 ), and the adjuvant therapy based on 5-FU is essential to CRC patients in stage II-IV after radical surgery, which could prolong the survival time of CRC patients ( Wilkinson et al, 2010 ; Miller et al, 2019 ; Huang X et al, 2022 ). The emergence of chemoresistance remains a significant barrier to long-term benefit ( Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate an increased sensitivity to certain drugs among TNBC patients classified in the high-risk group. RBP7 may be used as a tumor microenvironment regulator to induce 5-fluorouracil resistance, affecting the prognosis of patients with colorectal cancer [ 55 ]. Docetaxel activates the antitumor immune response in a CGA/STING-dependent manner and promotes T-cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Xingxing Huang and Xinbing Sui et al identi ed that some immune-related genes (HSPA8, RARB, RABEP2, ICAM2, CHGB, GALP, RBP7 et al) were associated with 5-Fu resistance and poor DFS and OS of CRC patients. And RBP7 may function as a tumor microenvironment regulator to induce 5-Fu resistance, thereby affecting the prognosis of CRC patients 25 . Besides, Guili Zheng and Qiang Wang et al found and demonstrated that CRC could obtain 5-Fu based chemotherapy by LINC01347/miR-328/LOXL2 axis, and LINC01347 could work as a prognostic biomarker and potential therapeutic target against 5-Fu based chemotherapy resistance of CRC 26 .…”
Section: Discussionmentioning
confidence: 99%